Transcriptome analysis reveals the effect of cold storage time on the expression of genes related to oxidative metabolism in Chinese black truffle - Zhang, Runji; Yang, Qiuyue; Yao, Xin; Fang, Zhirong; Wu, Xia; Lin, Qiao; Qing, Yuan (Frontiers in Nutrition, 2024)
Chinese black truffle (Tuber indicum) is a hypogenous fungus of great value due to its distinctive aroma. In this study, both transcriptome and physicochemical analyses were performed to investigate the changes of nutrients and gene expression in truffle fruiting bodies during cold storage. The results of physicochemical analysis revealed the active metabolism of fruiting bodies in cold storage, showing the decreased contents of protein and soluble sugar, the variations in both polyphenol oxidase activity and total phenol content, and the detrimental effect of reactive oxygen species production caused by heavy metals (cadmium and lead) in truffles. Transcriptome analysis identified a total of 139,489 unigenes. Down-regulated expression of genes encoding the catalase-like domain-containing protein (katE), glutaredoxin protein (GRX), a copper/zinc superoxide dismutase (Sod_Cu), and aspartate aminotransferase (AAT) affected the degradation metabolism of intracellular oxides. Ribulose-5phosphate-3-epimerase (RPE) was a key enzyme in response to oxidative stress in truffle cells through the pentose phosphate pathway (PPP). A total of 51,612 simple sequence repeats were identified, providing valuable resources for further genetic diversity analysis, molecular breeding, and genetic map-ping in T. indicum. Transcription factors GAL4 and SUF4-like protein were involved in glucose metabolism and histone methylation processes, respectively. Our study provided a fundamental characterization of the physicochemical and molecular variations in T. indicum during the cold storage at 4 °C, providing strong experimental evidence to support the improvement of storage quality of T. indicum.